Turbat al-Ḥusayn: Modern Presentation of an Early Shīʿī Practice - S. M. Hadi Gerami; Zinab Aghagolizadeh (Religions)
This article explores the historical and contemporary evolution of turbat al-ḥusayn, the sacred soil of Karbala, as a central element in shaping Shīʿī identity and ritual practices. From the early Islamic centuries, turbat al-ḥusayn has served not only as a symbol of healing and blessing but also as a key component of Shīʿī collective memory. The paper examines the development of turbat rituals across three significant periods: pre-Safavid, post-Safavid, and post-revolutionary Iran. During the pre-Safavid period, including the medieval Islamic centuries, the sanctification of turbat evolved through the efforts of Shīʿī Imams such as al-Bāqir and al-Ṣādiq, who integrated it into the theological framework of wilāyah (guardianship) and Shīʿī ritual practices. This period also witnessed the gradual codification of its ritualistic and medicinal uses in foundational Shīʿī texts. During the Safavid era, turbat became institutionalized as a marker of Shīʿī identity, with its economic significance expanding through the production of prayer tablets and rosaries. Following the 1979 Islamic Revolution in Iran, turbat was reinterpreted as a symbol of martyrdom and resistance, aligning with revolutionary ideologies and narratives that paralleled the sacrifices of Karbala with contemporary struggles. The COVID-19 pandemic introduced new dimensions to turbat’s role, with its promotion as a medicinal remedy by religious figures, despite lacking historical precedent in traditional Shīʿī teachings. These developments illustrate how turbat al-ḥusayn continues to be dynamically recontextualized in response to modern challenges. The study concludes that turbat al-ḥusayn transcends its ritualistic and spiritual origins, serving as a flexible and enduring symbol of Shīʿī identity. Its evolving interpretations underscore the interplay between tradition and modernity, highlighting its ongoing relevance in both devotional life and socio-political discourse.